An image processing application for quantitative cross-correlative microscopy for large cell-populations: a gold nanoparticle radiosensitisation study. (2nd August 2017) - Turnbull, Tyron; Douglass, Michael; Bezak, Eva; Thierry, Benjamin; Kempson, Ivan
Abstract : A robust analysis script was developed in MATLAB for cross-correlative quantification of internalised gold nanoparticle (AuNP) uptake in a large number of individual cells with the corresponding number of DNA double-strand breaks (DSBs) in the same cells. The correlation of inorganic NP content with a biological marker at the single-cell level will aid in the elucidation of mechanisms of NP radiosensitisation. PC-3 cells were co-cultured with AuNPs and irradiated using an iridium-192 source. AuNP uptake was measured using synchrotron X-ray fluorescence (XRF) and DSBs imaged via confocal microscopy. MATLAB 2016a was used to develop a script to cross-correlate the two imaging modalities and quantify both DSBs and internalised AuNP content in the same cell. Various user-defined options written into the script give a high degree of versatility, which can account for a large number of variables in experimental parameters and data acquisition. The analysis procedure is flexible and robust, which gives consistent consideration to the wide spectrum of potential input image/data sets. Quantitative correlative microscopy was achieved with a custom MATLAB script used to correlate γH2AX foci (a marker of DNA DSBs) from confocal microscopy with AuNP content acquired using synchrotron XRF at the single-cell level. The script can be extended to a broad range of multi-modality imaging spectroscopies.